Nutrition, sarcopenia and frailty: an Asian perspective - Woo, Jean; Ong, Sherlin; Chan, Ruth; Li, Liz; Sun, Jianqin; Chan, Yoke Mun; Wee, Shiou Liang; Thu, Nghiem Nguyet; Thang, Pham; Setiati, Siti; Huang, Yi Chen; Wahlqvist, Mark L.; et al. (KeAi Communications, 2019)
Despite a growing body of evidence that nutrition plays a key role in the pathophysiology, prevention and intervention programs of frailty and sarcopenia, as well as in promoting brain health, the awareness and the need to study the relationship between nutrition and functional goals of healthy ageing have not received as much attention or support from research or policy makers. This review reports on the state of knowledge relating to availability of nutrition survey data for older people relating to prevalence of frailty and sarcopenia in Asia, using data from Netherlands for comparison. Data were obtained from a meeting of a group of nutrition experts from Asia supplemented by literature search using key terms of nutrition, frailty, and sarcopenia. Although nutrition surveys may be carried out regularly in several countries, surveys are mainly carried out for the general adult population rather than specifically among the elderly population, and little data is available relating to the impact of nutrition on sarcopenia and frailty. There is an urgent need for more nutritional data relating to maintaining function with age as opposed to disease prevention, to guide health promotion policies and clinical management of increasingly older population and patients. A shift in the gathering of national nutrition data may need to include such functional measurements in relation to older people, as the latter forms the rapidly growing sector of ageing populations world-wide.